Keefektifan Model Pembelajaran Relating Expriencing Applying Cooperating Transfering (REACT) Berbantuan Media Corner Box Berbasis Pendekatan RME terhadap Pemahaman Konsep Matematika - Esa Cintya Fidini; Zulmi Roestika Rini (Departement of Mathematics Education, 2024)
This research aims to determine the effectiveness of the Relating, Expriencing, Applying, Cooperating and Transferring (REACT) learning model assisted by Corner Box media based on the Realistic Mathematics Education (RME) approach towards understanding concepts. This type of research is a quasi experimental design with the form of a nonequivalent control group design. The population in this study were all students at SD Negeri Susukan 01. The sampling technique used a non-probability sampling technique taken by purposive sampling. The research sample was classes IVA and IVB at SD Negeri Susukan 01. Data collection techniques in this research were test and non-test techniques. The test technique uses pretest and posttest while the non-test technique uses observation, questionnaires and documentation. Data analysis techniques include normality test, homogeneity test, one way anova test, simple linear regression test, independent sample t test and paired sample t test. The results of the research show: (1) There are differences in students' conceptual understanding abilities regarding the use of the REACT model assisted by Corner Box media based on the RME approach, proven by a significance level of 0.002 and 0.002 < 0.05 using an independent test sample t test and one way anova test (2) There is an influence of using the REACT model assisted by Corner Box based on the RME approach on the ability to understand concepts, proven by a significance level of 0.004 < 0.05 using the regression test simple linear (3) REACT model assisted by Corner Box based on the RME approach is able to improve the ability to understand concepts, proven by the significance level of 0.000 < 0.05 using the paired sample t test. The conclusion of this research is that the REACT model assisted by Corner Box based on the RME approach is effective in students' ability to understand concepts.